Pengaruh Penerapan Good Corporate Governance Terhadap Tata Kelola Club Sepakbola - Firmansyah, Ericko Dendy Akbar; Wawan Ardiansyah; Mohamad Djasuli (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
This study aims to determine the implementation of good corporate governance in football club governance, readiness in implementing good corporate governance in football governance. This research uses qualitative research. Football is a new industry that promises a lot of business potential in it. Correct club management is needed so that stakeholders are able to gain trust. One of the ways for clubs to gain the trust of their stakeholders is by fully implementing GCG principles at the club. . From this research, it can be concluded that football in Indonesia is still not fully appropriate in implementing GCG principles in its governance, there is still a lot of infrastructure and soft-structure that has not been fulfilled by clubs to be able to apply GCG principles to the fullest.